(untitled) (Kairaranga, 2010)
Children and young people with disabilities educated in their local school may need services to get equal access to the curriculum. To ensure that any educationally- relevant services achieve the best outcomes, the students’ own voices and perspectives should also be included. This paper introduces the School Setting Interview (SSI), an interview-based assessment that helps occupational therapists to understand the barriers to, and facilitators of, inclusion from the student’s perspective. This information added to that identified by the teaching team and the parents/caregivers, can only lead to a “fuller picture” which all the team can draw from when determining issues and identifying potential strategies to address.